Evaluation of Behavior of Hybrid Beam Combining Steel Inverted T-Section and RC Flange - Badache, Hacene; Mezhoud, Samy; Melhem, Abdul Qader (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper deals with flexural investigation of a type of steel-concrete composite beam structure able to provide an adequate bond between steel and concrete elements through the application of a simple steel reinforcement shear connector design, steel reinforcing bars bent into L-shapes. The cross sections involve inverted steel T-beam being embedded within reinforced concrete (RC) flange of the slab.
Keywords: hybrid beam; composites; steel-concrete; inverted T-beam; L-shaped connectors; belka hybrydowa; kompozyt; stal-beton; belka typu T; złącze